Synthesis of MoS2-based nanostructures and their applications in rechargeable ion batteries, catalysts and gas sensors: a review. Issue 30 (6th July 2022) - Sun, Wei; Zhang, Yaofang; Kang, Weimin; Deng, Nanping; Wang, Xiaoxiao; Kang, Xiaoying; Yan, Zirui; Pan, Yingwen; Ni, Jian
Abstract : This article mainly describes the preparation and application of MoS2 and MoS2 based composites in batteries, catalysts and gas sensors. Abstract : Molybdenum disulfide (MoS2 ) is a two-dimensional (2D) layered material with a graphene-like structure that has attracted attention because of its large specific surface area and abundant active sites. In addition, the compounding of MoS2 with other materials can enhance the performance in applications such as batteries, catalysts, and optoelectronic devices, etc. MoS2 is prepared by various methods, among which chemical deposition and hydrothermal methods are widely used. In this review, we focus on summarizing the applications of MoS2 and MoS2 composite nanomaterials in rechargeable ion batteries, catalysts for water splitting and gas sensors, and briefly outline the preparation methods.